Certain Problems of Forming Organizational Principles of National Youth Associations in Ukraine in 1917 - Khoroshev, Olexander (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 1970)
The article focuses on the research of the organizational principles which formed the basis for the earliest youth groups created in 1917 after the overthrow of the Russian autocracy. It also determines how the political situation of that time influenced the formation of the youth movement. Special attention is paid to analyzing relationships of parties and youth groups which had politically diverse orientations. They considered creation of an all-Ukrainian mass youth organization to be the main purpose of their activity. It was the solution of the above-mentioned problem that the organizational activity of youth associations was focused on.